Hybrid system energy simulation for housing - Agus Junaidi; Rahmaniar Rahmaniar; Suwarno Suwarno; Catra Indra Cahyadi; Wanapri Pangaribuan; Hot Marindo Hutabarat; Arsita Devi Tambunan; Albert Panjaitan (International Journal of Applied Power Engineering (IJAPE), 2026)
Fossil fuel power plants are still used as a source of energy around the world and have a significant impact on emissions and environmental pollution. To reduce these emissions, renewable energy offers a solution that can be applied in future housing. This study proposes a simulation using HOMER to determine the most cost-effective composition of hybrid renewable energy systems in housing. This simulation can combine photovoltaic (PV) systems, wind power (WP), and a converter that functions to change DC to AC from PV to obtain an alternating current (AC) system. The hybrid combination of PV and WP proves to be the most appropriate and economical choice at the research location. The results of the study showed that the installation of a hybrid system in housing, with an initial investment cost of IDR 107,474.43 million and an annual operating cost of IDR 22,540.23 million, is 41% lower than conventional fossil fuel-based systems. Research data shows that the project's payback period is estimated to be around 11 years. These findings can be recommendations for similar systems in regions with similar contours and geography. Apart from that, positive monetary impacts can provide incentives for policymakers to implement similar hybrid systems, thereby contributing to the goal of global emissions neutralization.